2011
DOI: 10.1177/147323001103900410
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Hepatic Liver X Receptor α-and Sterol Regulatory Element Binding Protein-1c-Mediated Lipid Disorder in the Pathogenesis of Non-Alcoholic Steatohepatitis in Rats

Abstract: Liver X receptor a (LXRa) and sterol regulatory element binding protein-1c (SREBP-1c) were studied in rats with nonalcoholic steatohepatitis (NASH) induced by a high-fat diet. Forty 5-week-old rats were fed either a high-fat diet (n = 30) or a normal diet (n = 10) for 9, 13 or 17 weeks. The mRNA and protein levels for LXRa and SREBP-1c were measured at each time point, as was fatty acid synthase (FAS) activity and the serum levels of free fatty acid (FFA) and triglyceride (TG). The mRNA and protein levels for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 51 publications
2
13
0
Order By: Relevance
“…Moreover, the role of SREBP‐1c in de novo lipogenesis and NAFLD pathogenesis is well acknowledged and has been suggested as a potential therapeutic target . Thus, the LXR‐α/SREBP‐1c signaling may contribute to the development of NAFLD . Our result exhibited that Q3GA dose‐dependently decreased SREBP‐1c and its downstream key gene FAS mRNA expression in in vitro and in vivo NAFLD models.…”
Section: Discussionsupporting
confidence: 51%
“…Moreover, the role of SREBP‐1c in de novo lipogenesis and NAFLD pathogenesis is well acknowledged and has been suggested as a potential therapeutic target . Thus, the LXR‐α/SREBP‐1c signaling may contribute to the development of NAFLD . Our result exhibited that Q3GA dose‐dependently decreased SREBP‐1c and its downstream key gene FAS mRNA expression in in vitro and in vivo NAFLD models.…”
Section: Discussionsupporting
confidence: 51%
“…3d), perhaps as a consequence of hepatic lipid metabolism modulation by PTX. The expressions of FASN and SREBP-1c are considered key factors for the progression of NAFLD/NASH (Ai et al, 2011;Blaslov et al, 2014). Our present study showed that PTX treatment reduces hepatic TG content, ameliorates hepatic steatosis, and decreases FASN mRNA and protein levels in the liver ( Fig.…”
Section: Discussionmentioning
confidence: 81%
“…Hence, it is believed to be a determinant of the maximal capacity of a tissue (the liver in particular) to synthesize fatty acids by de novo lipogenesis. Increases in FAS levels are attributed to elevation of serum levels of TG and NFEAs as well as liver TG31. Hence, downregulation of FAS expression might lead to a reduction in lipid levels in the liver and serum in Benifuuki-fed mice.…”
Section: Discussionmentioning
confidence: 99%